The role of intraseasonal variability at mid‐high latitudes in regulating Pacific blockings during boreal winter. (23rd April 2017) - Yang, Shuangyan; Li, Tim
ABSTRACT: By using daily National Centers for Environmental Prediction‐Department of Energy reanalysis data from 1979 to 2015, we investigated the connection between Pacific blockings and mid‐high latitude atmospheric intraseasonal oscillation (ISO) at 500 hPa in boreal winter. The ISO perturbation over a key area of 150 ° E–155 ° W, 60 ° –75 ° N is most co‐variated with Pacific blockings. The averaged geopotential height over this key area exhibits a statistically significant 10–35‐day periodicity. The ISO perturbation associated with the Pacific blocking activity shows pronounced westward propagation. The perturbation initiates at about 120 ° W, triggered by intraseasonal wave energy accumulation. A geopotential tendency diagnosis reveals that the time change rate of the geopotential height over the key area is primarily attributed to the advection of planetary vorticity by the ISO meridional flow. A mechanism is put forward in which the westward‐propagating ISO perturbations induce a blocking over the Pacific sector. When a strong northward ISO flow arrives in the key area, it acts against the gradient of planetary vorticity, leading to a negative vorticity advection. This negative advection tends to strengthen local anticyclonic vorticity and geopotential height anomalies. Thus, the westward‐propagating ISO meridional flow plays an active role in inducing the low‐frequency blocking activity over the Pacific sector.